FLT3 mutations in acute myeloid leukemia: Therapeutic paradigm beyond inhibitor development - Kiyoi, Hitoshi; Kawashima, Naomi; Ishikawa, Yuichi (Cancer science, 2020)
FMS‐like tyrosine kinase 3 (FLT3) is a type III receptor tyrosine kinase that plays an important role in hematopoietic cell survival, proliferation and differentiation. The most clinically important point is that mutation of the FLT3 gene is the most frequent genetic alteration and a poor prognostic factor in acute myeloid leukemia (AML) patients. There are two major types of FLT3 mutations: internal tandem duplication mutations in the juxtamembrane domain (FLT3‐ITD) and point mutations or deletion in the tyrosine kinase domain (FLT3‐TKD). Both mutant FLT3 molecules are activated through ligand‐independent dimerization and trans‐phosphorylation. Mutant FLT3 induces the activation of multiple intracellular signaling pathways, mainly STAT5, MAPK and AKT signals, leading to cell proliferation and anti–apoptosis. Because high‐dose chemotherapy and allogeneic hematopoietic stem cell transplantation cannot sufficiently improve the prognosis, clinical development of FLT3 kinase inhibitors expected. Although several FLT3 inhibitors have been developed, it takes more than 20 years from the first identification of FLT3 mutations until FLT3 inhibitors become clinically available for AML patients with FLT3 mutations. To date, three FLT3 inhibitors have been clinically approved as monotherapy or combination therapy with conventional chemotherapeutic agents in Japan and/or Europe and United states. However, several mechanisms of resistance to FLT3 inhibitors have already become apparent during their clinical trials. The resistance mechanisms are complex and emerging resistant clones are heterogenous. Further basic and clinical studies are required to establish the best therapeutic strategy for AML patients with FLT3 mutations. Several mechanisms of resistance to FLT3 inhibitors have already become apparent during their clinical trials. The resistance mechanisms are complex and emerging resistant clones are heterogenous.